Dopamine decreases expression of type-1 angiotensin II receptors in renal proximal tubule. - Cheng, H F (1996)
Systemic and/or locally produced angiotensin II stimulates salt and water reabsorption in the renal proximal tubule. In vivo, dopamine (DA) may serve as a counterregulatory hormone to angiotensin II's acute actions on the proximal tubule. We examined whether dopamine modulates AT1 receptor expression in cultured proximal tubule cells (RPTC) expressing DA1 receptors. Dopamine decreased basal RPTC AT1 receptor mRNA levels by 67 +/- 7% (n = 10; P < 0.005) and decreased 125I-angiotensin II binding by 41 +/- 7% (n = 4; P < 0.05). The DA1-specific agonist, SKF38393 decreased basal AT1 receptor mRNA levels (65 +/- 5% inhibition; n = 5; P < 0.025), and the DA1-specific antagonist, SCH23390 reversed dopamine's inhibition of AT1 receptor mRNA expression (24 +/- 10% inhibition; n = 8; NS) and angiotensin II binding (5 +/- 15%; n = 4; NS). DA2-specific antagonists were ineffective. In rats given L-DOPA in the drinking water for 5 d, there were decreases in both proximal tubule AT1 receptor mRNA expression (80 +/- 5%; n = 6; P < 0.005) and specific [125I] Ang II binding (control: 0.74 +/- 0.13 fmol/mg pro vs. 0.40 +/- 0.63 fmol/mg pro; n = 5; P < 0.05). In summary, dopamine, acting through DA1 receptors, decreased AT1 receptor expression in proximal tubule, an effect likely mediated by increased intracellular cAMP levels. Local dopamine production also led to decreased AT1 receptor expression, suggesting dopamine may reset sensitivity of the proximal tubule to angiotensin II.